2021
DOI: 10.3390/polym13060868
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Biodegradable Polymers via Termination of Ring-Opening Polymerization by Acyl Chlorides

Abstract: Aliphatic polyesters are an important class of polymeric materials for biomedical applications due to their versatile and tunable chemistry, biocompatibility and biodegradability. A capability of direct bonding with biomedically significant molecules, provided by the presence of the reactive end functional groups (FGs), is highly desirable for prospective polymers. Among FGs, N-hydroxysuccinimidyl activated ester group (NHS) and maleimide fragment (MI) provide efficient covalent bonding with –NH– and –SH conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The catalyst [(BHT)Mg(μ-OBn)(THF)] 2 [ 57 ] and 2,5-dioxopyrrolidin-1-yl 5-chloro-5-oxopentanoate ( NHS-Cl ) [ 19 , 58 ] were synthesized according to the described methods. 2,5-Dioxopyrrolidin-1-yl methyl glutarate ( NHS-OMe ), obtained previously from methyl glutarate [ 59 ], was prepared by us via methanolysis of SIG-Cl ; the protocol for the synthesis and NMR spectra of NHS-OMe are presented in Section S1 in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst [(BHT)Mg(μ-OBn)(THF)] 2 [ 57 ] and 2,5-dioxopyrrolidin-1-yl 5-chloro-5-oxopentanoate ( NHS-Cl ) [ 19 , 58 ] were synthesized according to the described methods. 2,5-Dioxopyrrolidin-1-yl methyl glutarate ( NHS-OMe ), obtained previously from methyl glutarate [ 59 ], was prepared by us via methanolysis of SIG-Cl ; the protocol for the synthesis and NMR spectra of NHS-OMe are presented in Section S1 in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…However, it is also possible to prepare PCL/Gt ES solution containing functionalized PCL macromolecules that are able to react with Gt amino groups, thus providing chemical binding between PCL and Gt macromolecules before ES molding. We recently developed an efficient method for the chain-end functionalization of polyesters via termination of the [(BHT)Mg(μ-OBn)(THF)] 2 ( Mg1 , Scheme 1 d) catalyzed ‘living’ ROP by NHS-substituted acyl chlorides and have shown that, when using 2,5-dioxopyrrolidin-1-yl 5-chloro-5-oxopentanoate ( NHS-Cl , Scheme 1 d), the best degree of the functionalization of PCL was achieved [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some macromolecules, there are also side branches, and their proportion depends on the polymerization degree of the starting OCL (from chain polymerization), the temperature of polycondensation, and the polycondensation degree. The kinetics of polycondensation was studied by 31 P NMR, and it was shown that the polycondensation process fulfills the Carothers equation. Moreover, it is a second-order process due to the intramolecular catalytic self-activation of the acidic groups.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Especially the ones on the reaction of the end groups inducing further functionalization with amine-and thiol-containing model compounds. 31 Another, general approach is based on hydrogen-bonding end groups directed to the thermoplastic elastomers. 32 Functionalized cyclic polymers were prepared using end groups via cyclopolymerization, 33 and functionalized PCL macromonomers were used for the synthesis of biodegradable nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation